PENGARUH MOTIVASI KERJA, KEPUASAN KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN - MIA SUMIATI; RR NIKEN PURBASARI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this study is to determine the effect of work motivation variable, job satisfaction, and work ability to employee performance. The object of this research is a company operating in the field of logistics or freight forwarder. The method used in this research is descriptive method and causality with multipleregression method to test the hypothesis. This research use Nonprobability Sampling technique with Saturation Sampling method. Respondents used in this study were 60 employees. Technique of collecting data by using questionnaire. The results showed that the motivation of work does not affect the performance of employees, but job satisfaction and work ability affect the employee performance.